PAMERAN LUKISAN YANG ERGONOMIS - Widnyana, I Gusti Nyoman (Universitas Pendidikan Ganesha, 2013)
The current exhibition of paintings is oriented more on business, so the objective of a person doing an exhibiting is to sell their paintings. It’s not something that is taboo, because the painter is also human who needs money for living expenses and for the cost of creating new paintings. unfortunately the comfort of the exhibition room is sometime forgotten. Visitors who initially come to see the exhibition and buy one of the paintings, they finally go out from the exhibition hall and cancel to buy the painting because they feel being uncomfortable in the hallKeywords: exhibition of painting, comfort of exhibition hall